Usefulness of the platelet-to-lymphocyte ratio in predicting long-term cardiovascular mortality in patients with peripheral arterial occlusive disease - Uzun, Fatih; Erturk, Mehmet; Cakmak, Huseyin Altug; Kalkan, Ali Kemal; Akturk, Ibrahim Faruk; Yalcin, Ahmet Arif; Uygur, Begum; Bulut, Umit; Oz, Kursat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Inflammation and increased platelet activation play a crucial role in the initiation and progression of atherosclerosis. Platelet-to-lymphocyte ratio (PLR) has recently been reported as a new independent predictor for major adverse cardiovascular events in cardiovascular diseases. Aim: To investigate the relation between PLR and cardiovascular mortality in patients with intermittent claudication or critical limb ischemia (CLI) or both. Material and methods : In our retrospective study, 602 consecutive patients who were admitted to a large tertiary hospital with the diagnosis of symptomatic peripheral arterial occlusive disease (PAOD) were included. Patients were divided into two groups according to their PLR as follows: high PLR (PLR > 142) and low PLR (PLR ≤ 142) groups. Results : During the follow-up period (median: 33.8 months (interquartile range: 21–45)), 131 deaths occurred out of 602 (21.8%) patients. Cardiovascular mortality was found to be significantly higher in the high PLR group compared to the low PLR group (31.6% vs. 17.2 %; p 142 and age were found to be independent predictors of long-term cardiovascular mortality in Cox regression analysis (hazard ratios (95% confidence interval): 1.03 (1.01–1.04) and 1.04 (1.02–1.06), p < 0.001 and p < 0.001, respectively). Conclusions : Platelet-to-lymphocyte ratio, which is one of the parameters of routine complete blood count, reflects increased inflammatory status, platelet activation and aggregation. PLR is a cheap and readily available marker that has the ability to improve risk stratification provided by conventional risk scores in predicting long-term cardiovascular mortality in PAOD.